The Impact of Adaptation to Pregnancy on Breastfeeding Self-Efficacy. - Eker, Aslı; Beşen, Meltem Aydın (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2021)
Background: This is a cross-sectional study conducted to evaluate the impact of adaptation to pregnancy on breastfeeding self-efficacy perception of women who applied to the Gynecology and Obstetrics Outpatient Clinic of a public hospital between March 1, 2018 and May 30, 2018. Methods: A total of 140 pregnant women were included in the study. Data were analyzed using Statistical Package for the Social Sciences 21 program. Shapiro-Wilk test was used for testing the normal distribution of the data, and the Levene test was used to test for homogeneity of variance. Student's t-test was used for comparing 2 independent means, 1-way analysis of variance was used for comparing >2 independent means, and Turkey posthoc test was used for pairwise comparisons. The Pearson correlation coefficient was calculated in the linear relationship between 2 continuous variables. Results: There was a statistically significant difference between the educational groups, spouses, and coeducation levels of the women and the mean scores of the Pregnancy Breastfeeding Self-Efficacy Scale. There was a statistically significant difference in the mean total Prenatal Self-Assessment Scale score by training groups (P = .004). In the second half of the pregnancy period, compliance with total Prenatal Self-Assessment Scale scores was found to increase (P = .019). A positive and weak relationship was found between the Pregnancy Breastfeeding Self-Efficacy Scale score and the Prenatal Self-Assessment Scale score (r = 0.202, P = .017). Conclusion: It has been found that the belief in breastfeeding self-efficacy increases significantly as women's compliance with pregnancy increases. In all polyclinics where pregnant women use actively, it is recommended that breastfeeding and breast milk training be widely conducted and that pregnant women are encouraged to use breast milk polyclinic and pregnancy school.